2004
DOI: 10.1210/jc.2004-0164
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Fall of Bone Formation and Transient Increase of Bone Resorption in the Course of High-Dose, Short-Term Glucocorticoid Therapy in Young Patients with Multiple Sclerosis

Abstract: Glucocorticoid (GC)-induced osteoporosis is the leading form of secondary osteoporosis. Bone loss can be rapid. However, longitudinal studies at the very beginning of treatment are scarce. Patients relapsing from multiple sclerosis are treated with high-dose, short-term iv GCs. A number of them are young, without concomitant disease affecting bone and with no substantial impairment of mobility. Such patients were selected for the present study. Thirteen patients suffering from multiple sclerosis [11 females, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
86
1
8

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(111 citation statements)
references
References 49 publications
15
86
1
8
Order By: Relevance
“…Accordingly, novel skeletonization and meshing algorithms are being performed on 3D images of the excavations produced in the presence of GCs in this study, and so far, they predict lower stiffness and increased fracture risk despite unchanged total resorbed area. (46) Furthermore, the serum levels of CTX are increased in GC-treated patients, (5,6) as are also the levels of CTX in the present pit assay in the presence of GCs. However, as stressed in the introduction, GC-induced osteoporosis is multifactorial (2,8) and also may result from increased OC survival and differentiation (9)(10)(11)13,15,16) and may be due both to direct effects and mediation by other cell types.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Accordingly, novel skeletonization and meshing algorithms are being performed on 3D images of the excavations produced in the presence of GCs in this study, and so far, they predict lower stiffness and increased fracture risk despite unchanged total resorbed area. (46) Furthermore, the serum levels of CTX are increased in GC-treated patients, (5,6) as are also the levels of CTX in the present pit assay in the presence of GCs. However, as stressed in the introduction, GC-induced osteoporosis is multifactorial (2,8) and also may result from increased OC survival and differentiation (9)(10)(11)13,15,16) and may be due both to direct effects and mediation by other cell types.…”
Section: Discussionmentioning
confidence: 57%
“…(10,17,18) One would expect that besides survival and differentiation, the resorptive activity of existing OCs is also stimulated by GCs because of the very early increase in bone-resorption markers induced by GCs in patients. (5,6) However, we are not aware of any mechanistic OC culture study supporting this view. Instead, primary OCs isolated from rat bones eroded the surfaces of bone slices less extensively in the presence of high-dose GC.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The severity of bone loss depends on dose and duration of treatment [12]. High doses of glucocorticoids, such as those typically used in treatment of MS exacerbations, have been shown to increase bone resorption and decrease bone formation [14][15]. Research suggests that the use of glucocorticoids is a predictor of bone loss in individuals with MS [2,7]; however, most studies do not assess the effect of long-term use of glucocorticoids on BMD in those with MS [9,[15][16].…”
Section: Introductionmentioning
confidence: 99%
“…High doses of glucocorticoids, such as those typically used in treatment of MS exacerbations, have been shown to increase bone resorption and decrease bone formation [14][15]. Research suggests that the use of glucocorticoids is a predictor of bone loss in individuals with MS [2,7]; however, most studies do not assess the effect of long-term use of glucocorticoids on BMD in those with MS [9,[15][16]. The association between long-term glucocorticoid use and BMD is still somewhat unclear because only one study has reported long-term effects and reported no association of high dose methylprednisolone on BMD in MS patients [17].…”
Section: Introductionmentioning
confidence: 99%